COMPARISON OF NON-VERBAL COMMUNICATION IN SASAKNESE (LOMBOK), VIETNAMESE, AND WESTERN - ARI SAPUTRA (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2020)
Non-verbal behavior is still becoming an interesting thing to observe about. It has special meaning of each expression which has unique side of it. This article focuses on comparison of some non-verbal behaviors in Sasaknese, Vietnamese, and Western. Before coming to the topic, in introduction this paper explains about definition of cross cultural communication and intercultural communication and how do both differ each other. Both are essential in developing communication especially nonverbal communication. The nonverbal behavior will create misunderstanding and different interpretation among different cultures and places. It is the problems in cross cultural communication where the nonverbal communication among countries are different views each others. Therefore through this paper, I want to say that understanding cross cultural differences in behavior is a perquisite for understanding communication.Keywords : Non-verbal communication, culturePerilaku nonverbal masih menjadi hal yang menarik untuk diperhatikan. Ini memiliki arti khusus dari setiap ekspresi yang memiliki sisi uniknya. Artikel ini berfokus pada perbandingan beberapa perilaku non-verbal dalam bahasa Sasak, Vietnam, dan Barat. Sebelum membahas topik ini, dalam pendahuluan makalah ini menjelaskan tentang definisi komunikasi lintas budaya dan komunikasi antarbudaya dan bagaimana keduanya berbeda satu sama lain. Keduanya sangat penting dalam mengembangkan komunikasi terutama komunikasi nonverbal. Perilaku nonverbal akan menciptakan kesalahpahaman dan perbedaan interpretasi antar budaya dan tempat yang berbeda. Ini adalah masalah dalam komunikasi lintas budaya dimana komunikasi nonverbal antar negara saling berbeda satu sama lain. Oleh karena itu melalui tulisan ini, saya ingin mengatakan bahwa memahami perbedaan lintas budaya dalam perilaku adalah suatu hal yang indah untuk memahami komunikasi.Kata kunci: Komunikasi non verbal, budaya